-2x+x+10=6-(2x+3x-8)

Simple and best practice solution for -2x+x+10=6-(2x+3x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+x+10=6-(2x+3x-8) equation:


Simplifying
-2x + x + 10 = 6 + -1(2x + 3x + -8)

Reorder the terms:
10 + -2x + x = 6 + -1(2x + 3x + -8)

Combine like terms: -2x + x = -1x
10 + -1x = 6 + -1(2x + 3x + -8)

Reorder the terms:
10 + -1x = 6 + -1(-8 + 2x + 3x)

Combine like terms: 2x + 3x = 5x
10 + -1x = 6 + -1(-8 + 5x)
10 + -1x = 6 + (-8 * -1 + 5x * -1)
10 + -1x = 6 + (8 + -5x)

Combine like terms: 6 + 8 = 14
10 + -1x = 14 + -5x

Solving
10 + -1x = 14 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
10 + -1x + 5x = 14 + -5x + 5x

Combine like terms: -1x + 5x = 4x
10 + 4x = 14 + -5x + 5x

Combine like terms: -5x + 5x = 0
10 + 4x = 14 + 0
10 + 4x = 14

Add '-10' to each side of the equation.
10 + -10 + 4x = 14 + -10

Combine like terms: 10 + -10 = 0
0 + 4x = 14 + -10
4x = 14 + -10

Combine like terms: 14 + -10 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| -3(6-5a)=9a+24 | | factorx^2+6x-27=0 | | -2(4t-4)+5t=8t-5 | | y+2y-12=3 | | (w+6)(w-1)+(12w+7)(w-1)=0 | | -.75z+.8z=0.05 | | 7k-14-2k=21 | | 500+22x=1204 | | 3x+7+x+30+1=70 | | 4t-9=1-t | | 12x-4=12(x-7) | | 4d+2-2=6+3d | | y-4x-3=0 | | 5x-20=25-4x | | 5(3x+2)=2(2x-6) | | -6y-2y=-12 | | 3z+12=2z+5 | | 5t-9=2t+3 | | 4-6n=32 | | 2x+24=30+x | | 2x+24=30+c | | -7x+4+3x=12 | | 0.25r-0.25=0.5-0.25r | | 10+3x=-5x+26 | | 2n^2+n-28=0 | | 3x-(10+4x)=-3x-8 | | x^2+5x+4+x^3=0 | | 1.15y+1.25y=15 | | 2+2x=a | | -33+10x=x+2x+100 | | 13=5-2y | | 2544c-0967b+-123c=x |

Equations solver categories